Introduction to Separation Index: Modelling of Rare Earth Element Extraction Complexity for Feasible Processing - Mohd Yusri, Mohd Yunus; Nurul Ain, Ismail; Badhrulhisham, Abdul Aziz; Anwaruddin, Hisyam; Mohd Aizuddin, Abdul Aziz (Penerbit Universiti Malaysia Pahang, 2016)
With the increasing demand from industries, the efficiency as well as the sustainability in extracting Rare Earth Elemnt (REE) from its main resources (mainly mining) has become very challenging. However, there is no specific study has been conducted particularly in optimizing the sequence of the extraction steps or reducing the complexity of separation stages when there are multiple choices of REE materials can be potentially extracted. In this light, this paper investigates the suitability of using the three main contributors of any Solvent Extraction (SX) system – separation factor value, material composition and number of processing stages (extraction and scrubbing), in specifically justifying the potential feasibility of the extraction pathways that has been initially selected for separation processing. In particular, the concept of Separation Index (SI) is introduced in correctly balancing the three corresponding factors of SX system, where ‘Art vs Science’ structure was used as the primary separation framework. In addition, two sets of Separation Factors - HDEHP-HCL and RE(III)-HCL-EHEHPA systems, are utilised to demonstrate the SI application. The results generally indicate that the proposed SI has sufficiently harmonizing the three main parameters of SX system, by which the low separation difficulty consists of the following criteria - relatively high SF value, relatively high material composition and relatively low number of stages. Through this work also, the ‘Árt vs Science’ is found favour the inter REE extraction rather than the intra separation. This is due to the chosen extractants generally shows low SF values mostly within the individual REE groups – light, medium and heavy REEs, respectively.